Exome Sequencing Highlights a Potential Role for Concealed Cardiomyopathies in Youthful Sudden Cardiac Death. (24th December 2021) - Neves, Raquel; Tester, David J.; Simpson, Michael A.; Behr, Elijah R.; Ackerman, Michael J.; Giudicessi, John R.
Abstract : Background: Sudden cardiac arrest (SCA) and sudden unexplained death (SUD) are feared sequelae of many genetic heart diseases. In rare circumstances, pathogenic variants in cardiomyopathy-susceptibility genes may result in electrical instability leading to SCA/SUD before any structural manifestations of underlying cardiomyopathy are evident. Methods: Collectively, 38 unexplained SCA survivors (21 males; mean age at SCA 26.4±13.1 years), 68 autopsy-inconclusive SUD cases (46 males; mean age at death 20.4±9.0 years) without disease-causative variants in the channelopathy genes, and 973 ostensibly healthy controls were included. Following exome sequencing, ultrarare (minor allele frequency ≤0.00005 in any ethnic group within Genome Aggregation Database [gnomAD, N=141 456 individuals]) nonsynonymous variants identified in 24 Clinical Genome Resource adjudicated definitive/strong evidence cardiomyopathy-susceptibility genes were analyzed. Eligible variants were adjudicated as pathogenic, likely pathogenic, or variant of uncertain significance in accordance with current American College of Medical Genetics and Genomics guidelines. Results: Overall, 7 out of 38 (18.4%) SCA survivors and 14 out of 68 (20.5%) autopsy-inconclusive, channelopathic-negative SUD cases had at least one pathogenic/likely pathogenic or a variant of uncertain significance nonsynonymous variant within a strong evidence, cardiomyopathy-susceptibility gene. Following American College of Medical Genetics and Genomics criterion variant adjudication, a pathogenic or likely pathogenic variant was identified in 3 out of 38 (7.9%; P =0.05) SCA survivors and 8 out of 68 (11.8%; P =0.0002) autopsy-inconclusive SUD cases compared to 20 out of 973 (2.1%) European controls. Interestingly, the yield of pathogenic/likely pathogenic variants was significantly greater in autopsy-inconclusive SUD cases with documented interstitial fibrosis (4/11, 36%) compared with only 4 out of 57 (7%, P <0.02) SUD cases without ventricular fibrosis. Conclusions: Our data further supports the inclusion of strong evidence cardiomyopathy-susceptibility genes on the genetic testing panels used to evaluate unexplained SCA survivors and autopsy-inconclusive/negative SUD decedents. However, to avoid diagnostic miscues, the careful interpretation of genetic test results in patients without overt phenotypes is vital.